Short‐term movement dynamics of the world’s largest sea cucumbers (genus Thelenota ) - Benjamin C. T. Gray; Luke A. Calvert; Steven W. Purcell (Marine Ecology, 2022)
Movement studies on marine animals can inform conservation and fishery management planning through data that explain likely dispersals and home‐ranging behaviours. Relatively few studies are documented for exploited marine invertebrates, despite many having a high ecological and commercial value. We assessed the diurnal movement patterns of Thelenota ananas and Thelenota anax , the world's largest sea cucumbers, which are highly exploited throughout the Indo‐Pacific. At two coral reef sites at Lizard Island, northern Australia, we tracked the 2‐hourly displacement of individuals from morning to nightfall. Movement of T . ananas was more reef‐associated and tortuous than T . anax . Displacement rates averaged 80 cm h −1 (±8 SE) for T . ananas and 73 cm h −1 (±20) for T . anax . Body size accounted for half of the variation in displacement for T . ananas . Mobility peaked in the late afternoon or early evening for both species, and animals tended to reverse their direction of travel after midday. The data reflect a pattern of animals meandering out from their reef shelters onto sandy lagoon floors to forage, before returning to the reefs. This empirical evidence offers further support that these holothuroids contribute to the formation of “reef halos”. The exceptionally high movement rates and patterns found in this study should inform the design of spatial management measures.